2020
DOI: 10.1051/e3sconf/202015405004
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Abandoned Petroleum Wells in Geothermal Energy Sector. Worldwide Trends and Experience

Abstract: Since the oil crises in the 1970s, geothermal resources have received much attention and researches aimed at its recognition have been conducted all around the globe. Nevertheless, the investment cost associated mainly with drilling works is a crucial limitation for the successful implementation of new geothermal projects. The radical solution affecting the cost effectiveness of any geothermal investments might be an adaptation of existing un-exploited boreholes of the oil and gas sector for geothermal purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The analyzed area of Carpathian Foredeep is well endowed with boreholes (abandoned or still operating, Figure 2), which translates into high possibility in terms of their potential reconstruction (although this depends directly on the technical condition of the hole and requires a pre-analysis/test) and destination for geothermal purposes. Theoretically, many of them could be suitable for the exploitation and injection of water after performing appropriate reconstruction operations [13,50] or for the implementation of different geothermal technology [28,35]. This is also a big advantage because, in the case of any geothermal investment, the drilling stage is the largest financial burden (even up to 80% [19])-the deeper the borehole is, the more expensive the projected investment.…”
Section: Discussionmentioning
confidence: 99%
“…The analyzed area of Carpathian Foredeep is well endowed with boreholes (abandoned or still operating, Figure 2), which translates into high possibility in terms of their potential reconstruction (although this depends directly on the technical condition of the hole and requires a pre-analysis/test) and destination for geothermal purposes. Theoretically, many of them could be suitable for the exploitation and injection of water after performing appropriate reconstruction operations [13,50] or for the implementation of different geothermal technology [28,35]. This is also a big advantage because, in the case of any geothermal investment, the drilling stage is the largest financial burden (even up to 80% [19])-the deeper the borehole is, the more expensive the projected investment.…”
Section: Discussionmentioning
confidence: 99%
“…The most crucial component of a deep geothermal heating system is the deep coaxial geothermal heat exchanger (CGHE), also known as coaxial borehole heat exchanger or wellbore heat exchanger. Nevertheless, drilling a borehole incurs the most significant financial investment of any geothermal system, accounting for up to 70% of the total investment costs on average, and therefore makes these systems economically unprofitable [7]. This prompts the desire to explore alternative solutions for efficient and economical acquisition of geothermal energy.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the number of AOGWs worldwide has reached approximately 30 million [16,27]. In addition, regions with favorable geothermal parameters are inherently rich in geothermal energy [7]. The conversion of those petroleum wells into geothermal heat exchangers can substantially reduce the investment costs of borehole drilling [16,24] and enhance the utilization of geothermal resources, while also mitigating environmental risks [28].…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative analysis conducted based on the Villafortuna-trecate oil field in Italy revealed that a 500 kW power plant could be sustainably serviced, with the capacity to generate a total of 25 GWh of electrical power in 10 years. Chmielowska et al [12] surveyed the world trend on the utilization of oil wells as geothermal energy sources and reiterated that it is increasingly being implemented in reality, particularly with the use of borehole heat exchangers. Duggal et al [13] identified the conversion technology choice, transient ambient conditions, and fluid handling system among the issues that should be handled well for maximum benefits from geothermal power production from an oil well.…”
Section: Introductionmentioning
confidence: 99%